2013
DOI: 10.1002/ange.201305010
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Oxidative C(CO)C(methyl) Bond Cleavage of Methyl Ketones to Aldehydes Catalyzed by CuI with Molecular Oxygen

Abstract: Bis zum Aldehyd: Eine kupferkatalysierte Umsetzung von Methylketonen zu Aldehyden wurde entwickelt. Die Methode kann für eine Vielzahl aromatischer und aliphatischer Methylketone verwendet werden und führt chemoselektiv zu Aldehyden, wobei lediglich Wasserstoff (H2) und Kohlendioxid (CO2) als Beiprodukte entstehen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 104 publications
(9 reference statements)
2
24
0
Order By: Relevance
“…Copper (II) acetate gave mixture of products (entry 7) and, with Copper Oxide only starting material was recovered (entry 8). In agreement with the earlier reports, 8 DMSO was found to be the appropriate solvent and no product formation was observed in solvents such as DMF, DCE and EtOH. Effectiveness of DMSO in aerobic oxidations may be attributed to its efficient metal-coordinating and catalyst stabilizing properties.…”
Section: Scheme 1 Copper Mediated Cleavage Of C-c Bond Adjacent To Csupporting
confidence: 92%
See 3 more Smart Citations
“…Copper (II) acetate gave mixture of products (entry 7) and, with Copper Oxide only starting material was recovered (entry 8). In agreement with the earlier reports, 8 DMSO was found to be the appropriate solvent and no product formation was observed in solvents such as DMF, DCE and EtOH. Effectiveness of DMSO in aerobic oxidations may be attributed to its efficient metal-coordinating and catalyst stabilizing properties.…”
Section: Scheme 1 Copper Mediated Cleavage Of C-c Bond Adjacent To Csupporting
confidence: 92%
“…Interestingly, this led to the formation of 3a through oxidative scission of both the methyl and the methylene groups on either side of keto group, with an ending of oxidation process at the aromatic terminal (table 4). Recently, Bi et al 8 and Jiao et al 5 also observed a similar cleavage process during the conversion of aralkyl methyl ketones to aromatic aldehydes and aromatic esters respectively. Noteworthy is that this is in contrast to the productivity of haloform pathway where the similar substrate undergoes the oxidation of only methyl group to afford aralkyl acids.…”
Section: Table 2 Synthesis Of Aromatic Acids From Aryl Methyl Ketonesmentioning
confidence: 74%
See 2 more Smart Citations
“…[2] Very recently we developed an efficient method to prepare 2-arylbenzothiazoles from phenylacetic acids and a-hydroxyphenylacetic acids with benzothiazoles under aerobic copper-catalyzed oxidation conditions. [4] As part of our continuing interest in prepare 2-arylbenzothiazoles, we speculated that 2-arylbenzothiazoles could be formed from aryl methyl ketones and benzothiazoles in the presence of CuI and O 2 based on our previous research and the above literature report. [4] As part of our continuing interest in prepare 2-arylbenzothiazoles, we speculated that 2-arylbenzothiazoles could be formed from aryl methyl ketones and benzothiazoles in the presence of CuI and O 2 based on our previous research and the above literature report.…”
mentioning
confidence: 99%